Assessment of Traditional Knowledge of Medicinal Plants Practiced by Rural Communities Residing Around Musk Deer National Park, Kashmir Himalaya, Pakistan - Hussain, Mumtaz; Alam, Jan; Shah, Ghulam Mujataba; Gul, Alia; Majid, Abdul; Shafqat, Nosheen; Khan, Sardar Muhammad Rafique (Ethnobotany Research and Applications, 2024)
Abstract Background: Traditional ethnomedicinal knowledge and robust association of native communities with plant biota are the key contributors to environmental sustainability. Its documentation becomes crucial because the communities residing in remote mountainous landscape having strong dependence on wild flora for medication of different ailments. The current study was conducted to document the traditional knowledge of medicinal plants species practiced by the inhabitants of Musk Deer National Park (MDNP) Azad Jammu and Kashmir, Pakistan. Methods: The data was acquired by administrating a total of 110 detailed semi structured interviews targeting respondents from different age groups, ethnic background, education and professions focusing on to capture the holistic picture of medicinal plants practiced with traditional wisdom. Data was analyzed using ethnobotanical indices like Use Value (UV), Relative Frequency of Citation (RFC), Informant Consensus Factor (IFC) and comparison with previous ethno medicinal literature. Results: In total 84 plant species belonging to 69 genera and 43 families were recorded used by resident of MNDP for 66 prominent therapeutic purposes. Family Asteraceae was the main contributor with 16 species followed by Polygonaceae and Fabaceae with 7 and 4 species, respectively. Roots were the dominant plants parts used with (30 species, 29.7 %), followed by leaves (19 species, 18.81 %) and whole plant (15 species, 14.85). Among six drug formulations, powder was commonly used (51 medications) followed by cooked (38), extract (28) and decoction (21) respectively. The maximum informant consensus factor (ICF) value was calculated for digestive system problem (0.98) followed by respiratory and skeletomuscular system problem (0.97 each). Taxus baccata, Juglans regia, Fragaria nubicola, Berberis lycium, Heracleum canescens, Pinus wallichiana, Saussurea costus, Thymus linearis, Aconitum heterophyllum, Picrorhiza kurroa and Jurinea himalaica were the most significant plants with the highest use value and relative frequency of citation. Conclusion: The ethno medicinal inventory reflects reasonable number of wild plants with valued traditional practicing knowledge by the local inhabitants in the form of primary and vital source of therapy. Therefore, it required to develop a comprehensive participatory conservation and management plan clearly reflecting mechanism for sustainable utilization of medicinal flora and further detailed investigation in Musk Deer National Park, Kashmir Himalaya, Pakistan. Keywords: Musk Deer National Park, Traditional knowledge, Ethnomedicine, Kashmir Himalaya